Discovering the potential of renewable energy from palm oil mill effluent: Environmental impacts, opportunities, and challenges in the development of biogas and bio-cng - Sagala, Donar; Frimawaty, Evi; Sodri, Ahyahudin (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Indonesia, as the largest palm oil-producing country in the world, will also produce palm oil mill effluent (POME). POME production from palm oil processing is faced with many environmental problems from the release of emissions. The development of new renewable energy in Indonesia needs to be increased to reduce dependence on fossil energy and commit to reducing greenhouse gas emissions. The purpose of this study is to discuss the potential for new renewable energy from the utilization of POME biogas energy and how the environmental impacts are caused as well as the opportunities and challenges of developing EBT from POME. Methods: This research analysis method is LCA, and descriptive. Findings: Total CO2 emission (eq) of biogas production from POME is -24.62 Kg CO2 (eq), eutrophication is -0.2188 Kg PO43- (eq) and acidification is 0.00552 Kg SO2 (eq). Biogas production from POME in Jambi Province is not optimal and has not been used optimally, the process efficiency is low, and the profitability is low. Conclusion: There is a need for a concept to utilize biogas energy that does not only focus on electrical energy but also as a renewable energy source such as bio-CNG which has wider use. Novelty/Originality of this article: The novelty of this research lies in the comprehensive analysis of the utilization of Palm Oil Mill Effluent (POME) as a renewable energy source that is not only limited to electrical energy but also includes the potential conversion of POME into bio-CNG as a more flexible and sustainable alternative.